Kulturowy wymiar fuzji i przejęć - Paulina Gawryszewska (Studia i Materiały)
The article is a review of the literature on the importance of organizational culture in mergers and acquisitions (M&A) processes at international companies. The author presents research on culture in organization and management fields and also discusses reasons for carrying out M&A. On the one hand the author considers culture one of main factors contributing to failure to merge on the other she shows its untapped potential in complicated conditions of changes in a company. Additionally the author defines what a successful integration process in M&A is giving examples of practical tools and theories which can be used in daily running of firm after a merger or an acquisition.